Identification of airborne microbiota in selected areas in a health-care setting in South Africa - Setlhare, Gaofetoge; Malebo, Ntsoaki; Shale, Karabo; Lues, Ryk (BMC Microbiology, 2014)
The role of bio-aerosols in the spread of disease and spoilage of food has been described in numerous studies; nevertheless this information at South African hospitals is limited. Attributable to their size, bio-aerosols may be suspended in the air for long periods placing patients at risk of infection and possibly settling on surfaces resulting in food contamination. The aim of the study is to assess the microbial composition of the air in the kitchen and selected wards at a typical district hospital in South Africa. Air samples were collected using the settle plates and an SAS Super 90 air sampler by impaction on agar. These microbial samples were quantified and identified using Matrix Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) and Analytic Profile Index (API). Results: Microbial counts were found to be higher in the fourth (≤6.0 × 101 cfu/m−3) sampling rounds when compared to the first (≥2 cfu/m−3), second (≤3.0 × 101 cfu/m−3) and third (≤1.5 × 101 cfu/m−3) sampling rounds. Genera identified included Bacillus, Kocuria, Staphylococcus, Arthrobacter, Candida, Aureobasidium, Penicillium and Phoma amongst others. The presence of these pathogens is of concern, attributable to their ability to cause diseases in humans especially in those with suppressed host immunity defenses. Furthermore, fungal genera identified (e.g. Candida) in this study are also known to cause food spoilage and fungal infections in patients. Conclusion: Results from this study indicate the importance of air quality monitoring in health-care settings to prevent possible hospital-acquired infections and contamination of hospital surfaces including food contact surfaces by airborne contaminants.
Published Article
Keywords: Air quality; Bio-aerosols; Health-care setting; MALDI-TOF MS